MUSTAQIL TA’LIM MASHG‘ULOTLARIDA ERKIN VOHIDOV ADABIY MEROSINI O‘RGATISH - Matyakupov, S.; Kudanova, Z. (SCIENCE and SOCIETY, 2018)
The article is devoted to the stady of the role of independent educational activities in teaching literary heritage of Erkin Vakhidov at academic lyceums. The author of the article also studies methods of teaching the creative work of the poet. There have been given theoretical and aesthetic results of the analysis on the example of the ode «Uzbegim» than is included in the text books of academic lyceums.